Geology and biogeochemical study in Sokor, Kelantan - Chang Shen Chang (2019)
Biogeochemistry is a multidisciplinary field that studies the complex relationship between geological and biological components. This research investigated the relationship of plants with ore elements in term of geochemistry and mineralogy. Geological mapping had been carried out: the identified lithology of the study area with 25 kilometres squared is argillaceous and calcareous units and the geological structures of folding which contribute to the current bed dipping and hydrothermal alteration through joint infilling has indicated an ore deposit region. In preliminary study, seven sets of soil samples were collected and analysed through Atomic Absorption Spectrophotometer to scope down the study area. Four sets of soil and plant samples had been collected and characterized through Fourier-Transform InfraRed Spectroscopy, X-ray methods (X-Ray Diffraction and X-Ray Fluorescence) and Inductively Coupled Plasma Mass Spectrometry respectively. The main composition of soil is clay minerals, kaolinite, dickite and pyrophyliite which can indicate argillic alteration and possible supergene enrichment for ore deposition. Phyllic alteration has also been found in area close to the study area with mineral assemblage of pyrite, quartz and sericite. There is also a relationship between the geomorphology, plant morphology and the ore element content in the soil: metal elements concentration is higher in lower elevation except aluminium and iron; the differential morphology of Melastoma malabathricum can indicate iron concentration in the soil. The findings of this research will be useful for diversifying current mineral exploration method in general and providing database for further investigation in the study area in specific.